GRAHANI ROGA - A CONCEPTUAL STUDY - Veena. G. Rao; Deepa.C. Patil (International Journal of Applied Ayurved Research, 2016)
The word Grahani can be understood in three ways i.e. grahani avayava, grahani dosha &grahani roga. Any deviation from the status of Samagnii.e. Mandagni, Teekshnagni& Vishamagniare called as Grahani dosha. This impaired agnileads to dooshana i.e. structural defect & functional impairment (vyaapaara vypareetya) of grahani (grahani rupa naadi) re-sulting in Grahani roga. According to modern medicine, the disorders of small intestine with repeated episodes of diarrhea alternate with constipation/formed stools associated with sys-temic features of malabsorption & Malnutrition can be considered as Grahani roga. The dis-ease is chirakari in nature with early amalakshanas & late Ojokshaya lakshanas.